De la Seguridad Democrática al Enfoque Territorial del Desarrollo: Recomendaciones desde el análisis de los referenciales de las políticas orientadas a superar el conflicto armado (2002 a 2023) (2024)
The Colombian armed conflict has mainly affected rural areas and resulted in half a million violent deaths and multiple human rights violations. Opinions on its origin are divided between the motivations of insurgent groups or structural conditions. Additionally, the conflict has been influenced by factors such as the lack of agrarian reform, the National Front, political underrepresentation, and illegal economies. The State and the FARC-EP guerrilla have been the main actors in this confrontation, and between 2002 and 2023, several public policies have been implemented to resolve the conflict. Analyzed from the perspective of Pierre Muller's policy frameworks, which examine the ideas behind their creation and application, two main frameworks emerge: "Democratic Security and Territorial Consolidation," present in the policies of Álvaro Uribe (2002-2010) and partially in the first term of Juan Manuel Santos (2010-2014); and "Development with a Territorial Approach," which emerged with the peace negotiations with the FARC-EP and the Integral Rural Reform (IRR) since 2010. Likewise, the implementation of the Peace Agreement by Iván Duque (2018-2022) showed a return to the first framework, and during Gustavo Petro's tenure, there are affinities with the IRR and the Total Peace policy. Finally, it is recommended that the current government advance in the implementation of the IRR, update the Regional Transformation Action Plans (PATR), rethink the Total Peace Policy in relation to illegal armed groups, and seek an agreement with the ELN.